Ideological War in Inclusive Twitter: #IndonesiaTanpaJIL versus Jaringan Islam Liberal - Hargyono Sindhunata (Antropologi Indonesia, 2013)
In early 2012, a civil-initiated movement called #IndonesiaTanpaFPI urged the government todisband an Islamic fundamentalist group called FPI (Front Pembela Islam) because of the violence to an Islamic minority group that FPI had commited earlier. #IndonesiaTanpaFPI heavily relied upon Twitter in organizing their movement, so when a counter-movement from the pro-FPI emerged, it was on Twitter as well; the counter-movement called themselves #IndonesiaTanpaJIL. This counter-movement believes that #IndonesiaTanpaFPI was actually initiated and organized by Jaringan Islam Liberal (JIL). Since then, #IndonesiaTanpaJIL and JIL have been fighting discursively on Twitter. This article concentrates on the formation of two religious publics constituted solely by their discourses articulated, particularly the topic related to suppressed of Islamic minority groups; namely: Ahmadiyah, Syiah, and Rohingya. Through tweets interpretation by seeking incision between intention of the text and model reader (that is constructed both by online and offline interaction), the writer has identified various discourse nexuses between ITJ and JIL. Both of the religious publics articulate interesting or controversial discourses on Twitter just to grasp the audience’s attention, because in the context of ideological war the number of supporters is the only important thing to bring their discourses to hegemonic domain. Furthermore, this article shows how the logic of modernity with its obsession to ideal order is a factor that can explain the culture of exclusivity inside a social arena that was designed for inclusivity.Keywords: religious public; Twitter; ideological war; hegemony; Indonesia Tanpa JIL; JaringanIslam Liberal